Exploring the biosorption of Methylene Blue dye onto acid treated sugarcane bagasse - Nharingo, Tichaona; Shoniwa, Viola; Hunga, Olindah; Shumba, Munyaradzi (2016)
The potential of acid treated sugarcane bagasse (ATSB) to remove methylene blue from waste waters was explored. Surface characterization of the biomass before and after MB sorption was achieved using FTIR spectrophotometer. The ATSB had surface functional groups, SiO2 and C were performed under optimized pH, contact time, biosorbent dosage and varying MB initial concentrations. The Langmuir, Freundlich, Temkin, Dubinin equilibrium data generated from the effect of MB initial concentration. The equilibrium data fitted the isotherms in the order: Langmuir > Freundlich = Halsey > Dubinin 0.9957 to 0.9621. The Langmuir isotherm based separation factor, R intensity, n, (1/n < 1) indicated sorption favorability between MB and ATSB with the Langmuir sorption capacity of 64.9351 mg/g. The Fre comprised of both macropores and micropores. The energy of sorption, E R and Temkin isotherms respectively indicated that the biosorption nature. ATSB can be used to remove MB from waste waters. However there is need to explore the effects of metal ions, anions and other dyes on the removal of MB by ATSB.